Biological effects and toxicity of diluted bitumen and its constituents in freshwater systems. Issue 11 (7th July 2015) - Dew, William A.; Hontela, Alice; Rood, Stewart B.; Pyle, Greg G.
Abstract Approximately 50 billion cubic meters of bitumen resides within the oil sands region of Alberta, Canada. To facilitate the transport of bitumen from where it is extracted to where it is processed, the bitumen is diluted with natural gas condensate ('dilbit'), synthetic crude from hydrocracking bitumen ('synbit'), or a mixture of both ('dilsynbit'). A primary consideration for the effects of diluted bitumen products on freshwater organisms and ecosystems is whether it will float on the water surface or sink and interact with the stream or lake sediments. Evidence from a spill near Kalamazoo, MI, in 2010 and laboratory testing demonstrate that the nature of the spill and weathering of the dilbit, synbit or dilsynbit prior to and during contact with water will dictate whether the product floats or sinks. Subsequent toxicological data on the effects of dilbit and other diluted bitumen products on freshwater organisms and ecosystems are scarce. However, the current literature indicates that dilbit or bitumen can have significant effects on a wide variety of toxicological endpoints. This review synthesizes the currently available literature concerning the fate and effects of dilbit and synbit spilled into freshwater, and the effects of bitumen and bitumen products on aquatic organisms and ecosystems. Dilbit is likely to provide ecological impacts that are similar to and extend from those that follow from exposure to lighter crude oil, but the prospect of bitumen settling after binding to suspended sediments elevates the risk for benthic impacts in streams and lakes. Copyright © 2015 John Wiley & Sons, Ltd.